Research On the Current Situation of Teaching English in Lower Secondary Schools In an Giang Province, Vietnam - Thang, Nguyen Bach; Dao, Nguyen Thi Hong (International Journal of Membrane Science and Technology, 2023)
The quality and effectiveness of teaching English in secondary schools depend on several factors, including the objectives, curriculum content, teaching methods, instructional organization, and the teaching capacity of the teachers. It also relies on the student’s motivation, awareness, and study attitude during English learning. Additionally, it is influenced by the organizational management mechanisms of the secondary schools. The author conducted a study to examine the current state of English teaching in secondary schools in An Giang province, aiming to shed light on the current status of English teaching activities in these schools.